2022
DOI: 10.3390/molecules27082535
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Suitability of Nineteen Lignins as Partial Polyol Replacement in Rigid Polyurethane/Polyisocyanurate Foam

Abstract: In this study, nineteen unmodified lignins from various sources (hardwood, softwood, wheat straw, and corn stover) and isolation processes (kraft, soda, organosolv, sulfite, and enzymatic hydrolysis) were used to replace 30 wt.% of petroleum-based polyol in rigid polyurethane/polyisocyanurate (PUR/PIR) foam formulations. Lignin samples were characterized by measuring their ash content, hydroxyl content (Phosphorus Nuclear Magnetic Resonance Spectroscopy), impurities (Inductively Coupled Plasma), and pH. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Although the addition of lignin into the foam increased reaction times, all the foams had acceptable reaction times for rigid foam synthesis. , Our previous study was the only other study that incorporated unmodified lignin into low-density rigid PUR/PIR foams. We used 19 technical lignins to replace 30 wt % of the petrochemical polyol with lignin and found that foams with higher reaction times (∼357 s) had significantly worse compression strengths, closed cell contents, and cell morphologies . All control and lignin-based foams were well below this reaction time by 27–75%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the addition of lignin into the foam increased reaction times, all the foams had acceptable reaction times for rigid foam synthesis. , Our previous study was the only other study that incorporated unmodified lignin into low-density rigid PUR/PIR foams. We used 19 technical lignins to replace 30 wt % of the petrochemical polyol with lignin and found that foams with higher reaction times (∼357 s) had significantly worse compression strengths, closed cell contents, and cell morphologies . All control and lignin-based foams were well below this reaction time by 27–75%.…”
Section: Resultsmentioning
confidence: 99%
“…After the foaming reaction characterization, foams were evaluated for apparent density (Table ). The apparent density of rigid foams is known to have a logarithmic correlation affecting most other foam properties outside the 30–60 kg/m 3 low-density range. ,,, The densities of lignin-based foams ranged from 41 to 54 kg/m 3 (Table ), falling within the low-density foam range, making the effect of density on foam properties insignificant. The increased density, compared to the control (35 kg/m 3 ), in lignin-based foams is likely caused by the use of solid lignin, which can delay foaming times (Figure ), increase polyol blend viscosity (Table ), and increase the degree of foam crosslinking. ,, Even so, all lignin-based foams had suitable apparent densities for rigid insulation and structural applications indicated by ASTM D7425 and E1730. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations